Efek Tata Kelola Perusahaan: Pilar Utama Dalam Manajemen Laba - Sudirman, Nengsi; Ramli, Muh; Pasally, Laurent Frisca Astutik; Andini, Andini (Universitas Musamus,Merauke,Papua, 2024)
This study aims to analyze the influence of the board of directors, board of commissioners, managerial ownership, and audit committee on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This study uses a purposive sampling method with certain criteria, so that 75 companies are obtained as samples. The data used are secondary data obtained from the company's annual report. Data analysis was carried out using the linear regression method with the help of the SPSS 26 application. The results of the study show that the board of directors, board of commissioners, and managerial ownership have a significant effect on earnings management. This shows that the existence and active role of the board of directors and board of commissioners, as well as a high level of managerial ownership, are able to control earnings management practices effectively. In contrast, the audit committee did not show a significant effect on earnings management, indicating that the function of the audit committee in preventing earnings management practices is not optimal. These findings provide practical implications for companies in improving more effective corporate governance, especially by strengthening the role of the board of directors and board of commissioners and improving the quality of managerial ownership. In addition, this study also provides theoretical contributions to the literature on corporate governance and earnings management.